Tumor Microenvironment Biosensors for Hyperpolarized Carbon-13 Magnetic Resonance Spectroscopy - Mu, Changhua (Mol Imaging Biol, 2021)
Hyperpolarization (HP) of a carbon-13 molecule via dynamic nuclear polarization (DNP) involves polarization at low temperature, followed by a dissolution procedure producing a solution with highly polarized spins at room temperature. This dissolution DNP method significantly increases the signal-to-noise ratio (SNR) of nuclear magnetic resonance (NMR) over 10,000-fold and facilitates the use of magnetic resonance spectroscopy (MRS) to image not only metabolism, but also the extracellular microenvironment. The extracellular tumor microenvironment (TME) closely interacts with tumor cells and stimulates their growth and metastasis. Thus, the ability to detect pathological changes in the TME is pivotal for the detection and study of cancers. This Review highlights the potential use of MRS to study features of the tumoral TME – elevated export of lactate, reduced interstitial pH, imbalanced redox equilibrium, and altered metal homeostasis. The promising outcomes of both in vitro and in vivo assays and suggest that DNP-MRS may be a useful technique to study aspects of the TME. With continued improvements, this tool has the potential to study the TME and provide guidance for accurate patient stratification and precise personal therapy.